2015
DOI: 10.1094/phyto-11-14-0334-fi
|View full text |Cite
|
Sign up to set email alerts
|

Resurgence of Pseudoperonospora cubensis: The Causal Agent of Cucurbit Downy Mildew

Abstract: The downy mildew pathogen, Pseudoperonospora cubensis, which infects plant species in the family Cucurbitaceae, has undergone major changes during the last decade. Disease severity and epidemics are far more destructive than previously reported, and new genotypes, races, pathotypes, and mating types of the pathogen have been discovered in populations from around the globe as a result of the resurgence of the disease. Consequently, disease control through host plant resistance and fungicide applications has bec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 95 publications
1
66
0
Order By: Relevance
“…Analyses of index of association also showed support for different lifestyles of these species, with indications of P. cubensis undergoing sexual reproduction and P. humuli being clonal. This is also supported by previous findings of the occurrence of mating types within P. cubensis and claims of homothallic lifestyle of P. humuli (Cohen et al, 2015; Cohen & Rubin, 2012). It should be noted that in laboratory settings, Runge & Thines (2012) demonstrated that there is some level of cross-infectivity of P. cubensis on Humulus lupulus and P. humuli on Cucumis sativus .…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Analyses of index of association also showed support for different lifestyles of these species, with indications of P. cubensis undergoing sexual reproduction and P. humuli being clonal. This is also supported by previous findings of the occurrence of mating types within P. cubensis and claims of homothallic lifestyle of P. humuli (Cohen et al, 2015; Cohen & Rubin, 2012). It should be noted that in laboratory settings, Runge & Thines (2012) demonstrated that there is some level of cross-infectivity of P. cubensis on Humulus lupulus and P. humuli on Cucumis sativus .…”
Section: Discussionsupporting
confidence: 90%
“…The prolific asexual sporulation of the pathogen on the leaf surface and the ease through which it is aerially dispersed from field to field also contribute to the pathogen’s damaging effects. Although the role of sexual reproduction and wild cucurbit hosts as inoculum sources still have not been thoroughly determined, epidemiological studies have helped develop control strategies (Lebeda & Cohen, 2011; Cohen et al, 2015; Holmes et al, 2015; Ojiambo et al, 2015; Wallace et al, 2014; Wallace, Adams & Quesada-Ocampo, 2015). To date, P. cubensis continues to cause major losses as vital fungicides lose efficacy (Ojiambo et al, 2015; Holmes et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Cohen & Rubin, ) have suggested an association between cucurbit host types and mating types of P. cubensis . There have also been reports of both mating types being able to infect the same host species suggesting that mating type and virulence might be genetically unlinked (Cohen et al., ). In the present study, all lineage II isolates were of the A1 mating type, while all lineage I isolates were of the A2 mating type.…”
Section: Discussionmentioning
confidence: 99%
“…Globally, populations of P. cubensis have changed and new virulent pathotypes have emerged (Lebeda et al ., , ; Cohen et al ., ; Kitner et al ., ; Ojiambo et al ., ). New pathotypes not only cause severe epidemics but substantially limit production of commercial cucurbit varieties and hybrids.…”
Section: Introductionmentioning
confidence: 98%
“…The pathogen is also highly aggressive and has demonstrated a high degree of adaptation that has enabled it to constantly increase its host range by infecting a wide range of cultivated and wild plants of the Cucurbitaceae family (Colucci et al ., ; Lebeda & Urban, ; Lebeda & Cohen, ; Lebeda et al ., ,b). Both mating types of P. cubensis and oospore formation have been reported in several countries (Cohen et al ., ), a characteristic that allows the pathogen to generate high levels of polymorphism within pathogen populations.…”
Section: Introductionmentioning
confidence: 99%